Core competencies for school leaders: insights from educational experts - Abunaser, Fathi M.; El-Din, Nesreen S. M. Salah; Al-Fahadi, Rashid S. (Frontiers in Education, 2025)
This study explores the essential competencies required for effective school leadership in Oman through a qualitative approach based on semi-structured interviews. Guided by a validated theoretical framework of core competencies for school principals, the research involved 50 experts from the Ministry of Education with specializations in educational supervision and administration. Data collection instruments were reviewed by specialists and pilot-tested to ensure clarity and relevance. The findings revealed a layered understanding of leadership competencies, where experts distinguished between general competencies expected of all school principals, specialized competencies commonly observed among high-performing leaders, and a refined set of critical competencies identified as essential for achieving effective and sustainable school leadership. Among these, ten key domains were emphasized, including instructional leadership, strategic planning, and communication skills. The study highlights noticeable gaps in current leadership practices and emphasizes the urgent need for structured, targeted professional development programs. These findings contribute to both local and international discourse on educational leadership and provide actionable insights for enhancing leadership preparation, school administration, and policy-making in the education sector.